Application of chemically synthesized conducting polymer-polypyrrole as a carbon dioxide gas sensor - Waghuley, S.A.; Yenorkar, S.M.; Yawale, S.S.; Yawale, S.P. (Sensors and actuators. B, Chemical, 2008)
A polypyrrole (PPy) has been a subject of many studies because it exhibits relatively high electrical conductivity, good environmental stability and versatility of synthesis. Pyrrole (Py), the monomer of PPy, has been polymerized via chemically oxidative polymerization in the presence of an oxidant (FeCl 3). Two samples of PPy in the form of odorless black powder were prepared by taking the weight ratios of Py to FeCl 3 of 0.429 (low) and 4.290 (high). At both ratios, the concentration of oxidant was kept constant. PPy-I sensor using PPy powder of a Py/FeCl 3 weight ratio of 0.429 and PPy-II sensor using PPy powder of a Py/FeCl 3 weight ratio of 4.290 were prepared by screen-printing technique on a glass substrate. For electrical contacts, electrodes of conducting silver paint were printed on adjacent sides of the sensor film. PPy-I and PPy-II sensors were used for CO 2 gas sensing investigation. Sensitivity of sensors at different concentrations of CO 2 gas was measured by a voltage drop method at room temperature (303 K). At certain higher concentration of CO 2 gas, a saturation effect was observed with both sensors. The response and recovery time were found short in PPy-II sensor. XRD, SEM, FTIR and TG/DTA were used to analyze the PPy powder. In the π-orbital overlap of neighboring molecules of the PPy structure, the π-electrons delocalize along the entire chain, which provides semiconducting and conducting properties. CO 2 molecules formed weak bonds with π-electrons of PPy. This causes an increase of resistance of the material in the presence of CO 2 gas.